Analysis of the factors and causes for which school desertion and absenteeism occur in public primary education institutions, in Chiquinquirá - Boyacá, in the year 2018 (2019)
Dropout is a problem in all education systems, one could say that globally, either in developing or industrialized countries. Most of the dropout studies show statistics that focus on the secondary levels of the education system, where students withdraw before the established age, without obtaining school certificates. In any case, material, social, family, individual and cultural factors basically determine dropout and truancy. In the present essay analyzes the factors and causes of dropout and truancy in public primary education institutions in Chiquinquirá - Boyacá, in 2018, as well as to analyze the policies and strategies used by the municipality regarding the problems of school dropout and truancy.